Trends in childhood leukaemia in Britain 1968-1978. - Stiller, C. A. (Nature Publishing Group, 1982)
Analysis of recent cancer registrations from Great Britain suggests that there has been an increase in the incidence of childhood acute lymphoid leukaemia for children born after about 1964. The increase is statistically significant for boys aged 0-4 years, and a lesser increase may also have occurred for girls in this age group. Reasons are given for believing that the increase is not purely an artifact attributable to improved registration procedures. Registration data from the Manchester Children's Tumour Registry, Denmark and Sweden support the suggestion that an increase h as occurred. It is not at present possible to say whether a change in incidence will also be seen at higher ages or will be confined to the youngest children, who may represent an aetiologically distinct sub-group. There is no obvious explanation for the findings reported here.